Answer:
x^4 + 5x^3 - 12x^2 + 5x + 1
Answer:
Wheres the question
Step-by-step explanation:
Answer:
g(h(x)) = [x + 3]^2 or x^2 + 6x + 9
Step-by-step explanation:
g[h(x)] signifies that h(x) is the input to g(x).
Writing out g(x) = x^2 and replacing "x" with [x + 3], we get:
g(h(x)) = [x + 3]^2 or x^2 + 6x + 9
Answer:
539
Step-by-step explanation:
The n th term of an arithmetic sequence is
= a₁ + (n - 1)d
Where a₁ is the first term and d the common difference
Here a₁ = 8 and d = 17 - 8 = 26 - 17 = 9, thus
= 8 + (9 × 59) = 8 + 531 = 539